How Do We Ensure the Quality of the Public Health Workforce? - Stephen B. Thacker, MD, MSc (Centers for Disease Control and Prevention, 2005)
The events of September 11, 2001, brought unprecedented attention to public health in the United States. The national response to these events included a large infusion of resources into the public health system that enhanced the capacity for the system to respond to terrorist threats and other public health emergencies. However, as illustrated by the emerging epidemics of obesity and diabetes in this country, a disproportionate burden of disease, death, and disability in this century will continue to be attributable to chronic disease. To address this burden effectively requires the development of a workforce with new skills in addition to maintenance of evolving traditional competencies. In 2002, the Institute of Medicine (IOM) published a report, Who Will Keep the Public Healthy?, that targeted the training needs of the public health workforce in this century (1). The IOM report included a recommendation for federal agencies to provide incentives for developing academicpractice partnerships.